Types of Inner Dialogues and Functions of Self-Talk: Comparisons and Implications - Oleś, Piotr K.; Brinthaupt, Thomas M.; Dier, Rachel; Polak, Dominika (Frontiers in Psychology, 2020)
Intrapersonal communication occurs in several modes including inner dialogue and self-talk. Dialogical Self Theory (Hermans, 1996) postulates a polyphonic self that is comprised of a multiplicity of inner voices. Internal dialogical activity implies an exchange of thoughts or ideas between at least two so-called “I-positions” representing specific points of view. Among the functions served by self-talk are self-criticism, self-reinforcement, self-management, and social assessment (Brinthaupt, Hein, & Kramer, 2009). This paper explores the relationships among different types of internal dialogues and self-talk functions. Participants included college students from Poland (n = 181) and the U.S. (n = 119) who completed two multidimensional measures of inner dialogue and self-talk. Results indicated moderately strong relationships between inner dialogue types and self-talk functions, suggesting that there is a significant overlap between the two modes of communication. We discuss several implications of these findings for exploring similarities and differences among different kinds of intrapersonal communication.